Calcium-Regulated Phosphorylation Systems Controlling Uptake and Balance of Plant Nutrients - Saito, Shunya; Uozumi, Nobuyuki (Frontiers in Plant Science, 2020)
Essential elements taken up from the soil and distributed throughout the whole plant play diverse roles in different tissues. Cations and anions contribute to maintenance of intracellular osmolarity and the formation of membrane potential, while nitrate, ammonium and sulfate are incorporated into amino acids and other organic compounds. In contrast to these ion species, calcium concentrations are usually kept low in the cytosol and calcium displays unique behavior as a cytosolic signaling molecule. Various environmental stresses stimulate increases in the cytosolic calcium concentration, leading to activation of calcium-regulated protein kinases and downstream signaling pathways. In this review, we summarize the stress responsive regulation of nutrient uptake and balancing by two types of calcium-regulated phosphorylation systems: CPK and CBL-CIPK. CPK is a family of protein kinases activated by calcium. CBL is a group of calcium sensor proteins that interact with CIPK kinases, which phosphorylate their downstream targets. In Arabidopsis, quite a few ion transport systems are regulated by CPKs or CBL-CIPK complexes, including channels / transporters that mediate transport of potassium (KAT1, KAT2, GORK, AKT1, AKT2, HAK5, SPIK), sodium (SOS1), ammonium (AMT1;1, AMT1;2), nitrate and chloride (SLAC1, SLAH2, SLAH3, NRT1.1, NRT2.4, NRT2.5) and proton (AHA2, V-ATPase). CPKs and CBL-CIPKs also play a role in C/N nutrient response and in acquisition of magnesium and iron. This functional regulation by calcium-dependent phosphorylation systems ensures the growth of plants and enables them to acquire tolerance against various environmental stresses. Calcium serves as the key factor for the regulation of membrane transport systems.